Epidemiology of asthma exacerbations and their relation with environmental factors in the Basque Country. Issue 6 (June 2015) - Altzibar, J. M.; Tamayo‐Uria, I.; De Castro, V.; Aginagalde, X.; Albizu, M. V.; Lertxundi, A.; Benito, J.; Busca, P.; Antepara, I.; Landa, J.; Mokoroa, O.; Dorronsoro, M.
Summary Background Asthma is a highly prevalent chronic inflammatory disease characterised by reversible airflow obstruction and hyperreactivity and inflammation of the airways. Factors that cause and/or trigger asthma attacks include host‐related factors (genetic predisposition, obesity and sex) and environmental factors (allergens, infections, occupational sensitisation, smoking status, pollution and diet). Objective To describe the epidemiology of asthma exacerbations (AEs) in the Basque Country and to explore its relationship with potentially associated environmental variables. We studied a total of 31 579 emergency department (ED) visits and 28 189 hospitalisations due to asthma. We describe the trends, incidence, seasonality and the influence of age and sex, as well as of exposure to NO2, CO, PM, O3, and pollen, temperature, relative humidity and flu status. We calculated the Pearson′s R correlation coefficient for the study variables. Results The incidence was 486 and 88.9 cases per 100 000 people for ED visits and hospitalisations, respectively. Slightly over half (53.5%) of the ED cases were male, while females represented 62.6% of the hospital admissions. Hospitalisations are tending to decrease in children and increase in over 64‐year‐olds. Peaks in cases occur at the beginning of autumn in children and in winter in adults. AEs were correlated positively with exposure to NO2, CO and to the influenza virus and negatively with temperature and exposure to O3. These relationships vary, however, with age and season. Conclusions and Clinical Relevance Rates of hospitalisation for AEs and trends in these rates over time are different in adults and children with the patterns varying by sex, season and environmental conditions.